TEKNIK INTERPRETASI HADIS DALAM KITAB SYARAH AL-HADIS - Sulaemang L Sulaemang (Jurnal Ilmiah Ilmu Ushuluddin, 2015)
Subul al-Salm, al-Shananis work accommodates the explanation of Bulugh al-Maram, the work of Ibn Hajaral-Asqalani that contain the Prophetic Hadith. Many moslems in the Islamic world use it to understand the meaningof some hadiths. As the explanation book (kitab syarh), Subul al-Salm certainly has some methods of interpretinghadiths. This article tried to explain al-Shananis methods in interpreting hadith. Actually it discussed about thebiography of Subul al-Salms author, the systematic of the book, and the interpretation methods that is used in thebook. After all, this article wants to give the reader a comprehensive representation of Subul al-Salm.